Interplay Between Reactive Oxygen Species and the Inflammasome Are Crucial for Restriction of Neospora caninum Replication - Mota, Caroline M.; Lima-Junior, Djalma de S.; Ferreira França, Flávia Batista; Aguillón Torres, Jhoan David; Barros, Patrício da Silva Cardoso; Santiago, Fernanda Maria; Silva, Joāo Santana; Mineo, José Roberto; Zamboni, Dario S.; Mineo, Tiago W. P. (Frontiers in Cellular and Infection Microbiology, 2020)
Neospora caninum poses as a considerable threat to animal health and generates significant economic impact in livestock production worldwide. Here, we have investigated the mechanism that underlies the participation of the inflammasome complex and Reactive Oxygen Species (ROS) in the regulation of immune responses during N. caninum infection. For that purpose, we used in vitro (bone marrow derived macrophages) and in vivo mouse models of infection. Our results show that NLRP3 and NLRC4 receptors, alongside with ASC and Caspase-1, are required for proper activation of the inflammasome during N. caninum infection. As expected, the engagement of these pathways is crucial for IL-1, IL-1, and IL-18 production, as well as the induction of pyroptosis. Our results also show that N. caninum induces ROS production dependent of the inflammasome assembly, which in its turn also depends on MyD88/NF-B-induced ROS to maintain its activation and, ultimately, lead to restriction of parasite replication.